2003
DOI: 10.1007/s00248-002-3005-9
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Growth Efficiency in the Tropical Estuarine and Coastal Waters of Goa, Southwest Coast of India

Abstract: Bacterial growth efficiency (BGE) is an index of organic carbon passing through bacteria in an aquatic system. BGE values of natural bacterioplankton assemblages were measured in tropical estuarine and adjacent coastal waters in Goa along the southwest coast of India. The BGE values for estuarine and coastal waters were 18 (+/-7.84%) and 11 (+/-4.19%), respectively. BGE in these waters were at the lower end of what is usually found in productive systems. This may be due to the high respiration rates. Further, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
41
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 31 publications
4
41
2
Order By: Relevance
“…The high variability in BP, BR, BCD and BGE, also observed in other tropical estuaries (GUENTHER et al, 2008;RAM et al, 2007), was already expected due to the high hydrodynamic complexity of this system (GUENTHER et al, 2015). Although the BP rates measured in Recife harbor were similar, on average, to other tropical and temperate estuaries (APPLE; DEL GIORGIO, 2007;NEWELL, 2012;GUENTHER et al, 2008;RAM et al, 2003), the BR rates were higher, leading to lower BGE (see Table 3). Bacterial respiration rates were more variable than BP rates and inversely correlated to BGE (see Table 2) which suggest that BGE variations are better explained by BR.…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations
“…The high variability in BP, BR, BCD and BGE, also observed in other tropical estuaries (GUENTHER et al, 2008;RAM et al, 2007), was already expected due to the high hydrodynamic complexity of this system (GUENTHER et al, 2015). Although the BP rates measured in Recife harbor were similar, on average, to other tropical and temperate estuaries (APPLE; DEL GIORGIO, 2007;NEWELL, 2012;GUENTHER et al, 2008;RAM et al, 2003), the BR rates were higher, leading to lower BGE (see Table 3). Bacterial respiration rates were more variable than BP rates and inversely correlated to BGE (see Table 2) which suggest that BGE variations are better explained by BR.…”
Section: Discussionmentioning
confidence: 57%
“…Temperatures at Recife harbor are high throughout the year (25-30 o C), which led to high bacterial production but even higher bacterial respiration rates. Indeed, previous studies performed in tropical estuarine waters showed lower BR rates (BR max =0.7 µM C h LEE et al, 2009;RAM et al, 2003). Nutrient availability also plays a major role in regulating bacterial carbon metabolism (ASMALA et al, 2014;BERGGREN et al, 2010;GASOL et al, 2009;KEMP, 2003).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Multiple lines of evidence suggest that Mandovi-Zuari tropical system is net heterotrophic especially in the monsoon season where respiration exceeds gross primary production, which can only occur when external subsidies of organic C support estuarine metabolism [39]. This study area forms a part of the Northern Indian Ocean (southeastern Arabian Sea) is characterized by extreme wind forcing and seasonal monsoon winds which are an annual recurring phenomenon in these estuaries [29].…”
Section: Introductionmentioning
confidence: 99%